SDG2 regulates Arabidopsis inflorescence architecture through SWR1-ERECTA signaling pathway - Liping Liu (Elsevier, 2021)
Summary: Inflorescence architecture is diverse in flowering plants, and two determinants of inflorescence architecture are the inflorescence meristem and pedicel length. Although the ERECTA (ER) signaling pathway, in coordination with the SWR1 chromatin remodeling complex, regulates inflorescence architecture with subsequent effects on pedicel elongation, the mechanism underlying SWR1-ER signaling pathway regulation of inflorescence architecture remains unclear. This study determined that SDG2 genetically interacts with the SWR1-ER signaling pathways in regulating inflorescence architecture. Transcriptome results showed that auxin might potentially influence inflorescence growth mediated by SDG2 and SWR1-ER pathways. SWR1 and ER signaling are required to enrich H2A.Z histone variant and SDG2 regulated SDG2-mediated H3K4me3 histone modification at auxin-related genes and H2A.Z histone variant enrichment. Our study shows how the regulation of inflorescence architecture is mediated by SDG2 and SWR1-ER, which affects auxin hormone signaling pathways.